Resolving fluorescence spectra of Maillard reaction products formed on bovine serum albumin using parallel factor analysis - Anne Bech Risum; Marta Bevilacqua; Chengkang Li; Kasper Engholm-Keller; Mahesha M. Poojary; Åsmund Rinnan; Marianne N. Lund (Food Research International, 2024)

Potentially harmful elements pollute soil and vegetation around the Atrevida mine (Tarragona, NE Spain) - L. Roca-Perez; R. Boluda; J. A. Rodríguez-Martín; J. Ramos-Miras; P. Tume; N. Roca; J. Bech (Environmental Geochemistry and Health, 2023)
Mining activity is one of the main sources to pollute soil, water and plants. An analysis of soil and plant samples around the Atrevida mining area in Catalonia (NE Spain) was preformed to determine potentially harmful elements (PHEs). Soil and plant samples were taken at eight locations around the mining area. The topsoil (0–15 cm) samples were analysed for physico-chemical properties by standard methods, by ICP-MS for Cd, Co, Cr, Cu, Fe, Ni, Pb and Zn, and were microwave-digested. Plant, root and shoot samples were digested separately, and heavy metals were analysed by AAS. Translocation factor (TF), biological concentration factor (BCF) and biological accumulation factor (BAF) were determined to assess the tolerance strategies developed by native species and to evaluate their potential for phytoremediation purposes. Soil pH was generally acid (5.48–6.72), with high soil organic matter (SOM) content and a sandy loamy or loamy texture. According to the agricultural soil values in southern Europe, our PHEs concentrations exceeded the toxicity thresholds. The highest root content of the most studied PHEs appeared in Thymus vulgaris L. and Festuca ovina L., while Biscutella laevigata L. accumulated more PHEs in shoots. The TF values were > 1 in B. laevigata L., but BAF obtained < 1, except Pb. B. laevigata L., and can be considered potentially useful for phytoremediation for having the capacity to restrict the accumulation of large PHEs amounts in roots and Pb translocation to shoots.

Urban agriculture and its biodiversity: What is it and what lives in it? - H. Royer; J.L. Yengue; N. Bech (Agriculture, Ecosystems & Environment, 2023)

Extent of introgressive hybridization in the Hermann’s tortoise (Testudo hermanni hermanni) from the south of France - N. Bech; D. Nivelle; S. Caron; J. M. Ballouard; V. Arnal; D. Arsovski; A. Golubović; X. Bonnet; C. Montgelard (European Journal of Wildlife Research, 2022)

Ex vivo diffusion-weighted MRI tractography of the Göttingen minipig limbic system - Johannes Bech; Dariusz Orlowski; Andreas N. Glud; Tim B. Dyrby; Jens Christian H. Sørensen; Carsten R. Bjarkam (Brain Structure and Function, 2020)

Phenotypic variation contrasts with genetic homogeneity across scattered sea snake colonies - N. Bech; T. Foucart; T. Fauvel; F. Brischoux; D. Bouchon; X. Bonnet (Journal of Biogeography, 2016)
Aim In philopatric species distributed across wide geographical areas, each population is influenced by local factors. We assessed the expected spatial genetic and phenotypic structure across a set of colonies of a highly philopatric sea snake. Location South Lagoon of New Caledonia, Western Pacific Ocean. Methods We used body size ( N = 4915 individuals) to assess phenotypic variations across 11 islet colonies of the amphibious sea kraits ( L. saintgironsi ) spread throughout the South Lagoon of New Caledonia. We also used 11 microsatellite markers in a subsample of 302 individuals to examine the demographic history and genetic structure. Results A major colonization event and rapid population expansion occurred during the mid‐Pleistocene. Mean body size increased significantly along the north–south gradient investigated, suggesting that each colony is relatively independent and responds to local conditions. However, our data revealed a total lack of genetic structure despite a substantial genetic diversity. Main conclusions A peculiar reproductive system likely underlies this pattern that combines a marked phenotypic gradient with a lack of geographical genetic structure. Gravid females from colonies scattered throughout the South Lagoon converge towards few communal coastal nesting sites to lay their eggs. Hatchlings disperse randomly in the lagoon and supply islets with recruits. This process homogenizes the overall genetic structure. However, because when settled snakes are philopatric, the mean body size of each colony presumably reflects the influence of local conditions. This system resembles those documented in various organisms (e.g. fish) but was not previously described in any amniotic lineage.

Genetic footprints reveal geographic patterns of expansion in Fennoscandian red foxes - Karin Norén; Mark J. Statham; Erik O. Ågren; Marja Isomursu; Øystein Flagstad; Nina E. Eide; Thomas Bjørneboe G. Berg; Lene Bech‐Sanderhoff; Benjamin N. Sacks (Global Change Biology, 2015)
Population expansions of boreal species are among the most substantial ecological consequences of climate change, potentially transforming both structure and processes of northern ecosystems. Despite their importance, little is known about expansion dynamics of boreal species. Red foxes ( Vulpes vulpes ) are forecasted to become a keystone species in northern Europe, a process stemming from population expansions that began in the 19th century. To identify the relative roles of geographic and demographic factors and the sources of northern European red fox population expansion, we genotyped 21 microsatellite loci in modern and historical (1835–1941) Fennoscandian red foxes. Using Bayesian clustering and Bayesian inference of migration rates, we identified high connectivity and asymmetric migration rates across the region, consistent with source‐sink dynamics, whereby more recently colonized sampling regions received immigrants from multiple sources. There were no clear clines in allele frequency or genetic diversity as would be expected from a unidirectional range expansion from south to north. Instead, migration inferences, demographic models and comparison to historical red fox genotypes suggested that the population expansion of the red fox is a consequence of dispersal from multiple sources, as well as in situ demographic growth. Together, these findings provide a rare glimpse into the anatomy of a boreal range expansion and enable informed predictions about future changes in boreal communities.

Isolation and characterization of the leucine-rich proteoglycan nyctalopin gene (cNyx) from chick - N. Torben Bech-Hansen; Josh Cockfield; Dan Liu; C. Cairine Logan (Mammalian Genome, 2005)

A summary of 20 CACNA1F mutations identified in 36 families with incomplete X-linked congenital stationary night blindness, and characterization of splice variants - Kym Boycott; Tracy Maybaum; Margaret Naylor; Richard Weleber; Johane Robitaille; Yozo Miyake; Arthur Bergen; Mary Pierpont; William Pearce; N. Bech-Hansen (Human Genetics, 2001)

A comparison of the effects of etodolac and ibuprofen on renal haemodynamics, tubular function, renin, vasopressin and urinary excretion of albumin and α-glutathione- S -transferase in healthy subjects: a placebo-controlled cross-over study - K. B. Svendsen; J. N. Bech; T. B. Sørensen; E. B. Pedersen (European Journal of Clinical Pharmacology, 2000)

Localization of a gene for incomplete X-linked congenital stationary night blindness to the interval between DXS6849 and DXS8023 in Xp11.23 - N. T. Bech-Hansen; Kym M. Boycott; Kathy J. Gratton; Daniel A. Ross; L. Leigh Field; William G. Pearce (Human Genetics, 1998)